Possible ways to solve the problem of overpopulation of the planet - Golovach, Alla A. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The historical and philosophical perspective of the emergence of the demographic problem of overpopulation as a global one is proposed. The article presents a socio-philosophical analysis of the problem of overpopulation and its consequences in the case of uncontrolled growth on the planet Earth. It is concluded that there is a need for an ontological perspective approach that fully takes into account the impact of the processes of population aging and the reduction of the labour force, as well as the costs associated with them. The obstacles that may be in the way of reducing the population in the state are identified: social, religious, migration, and political differences.
Keywords: global problems; overpopulation; demographic explosion; forecasting; demographic crisis